HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN TENDANGAN DOLLYO CHAGI (TENDANGAN MELINGKAR) ATLET TAEKWONDO PASKHAS KOTA PEKANBARU - Triastuti, Devfy; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s reachers suspect that power of leg musles athlete in Paskhas Pekanbaru not good enough. It scan see when taekwondo athlete joined the match and trials, reachers found less quickly of dollyo chagi, released into the opponent resulting in a kick under powered so the kick did not produce a point and otherwise an easy opponent to anticipate the attack given. The purpose of this research is to see the correlation of exsplosive power leg muscles with dollyo chagi kick of taekwondo athlete. Population in this research is all Pashkas Taekwondo Athlete of Pekanbaru amount 12 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 12 people. Research instrument measure power leg muscles used vertical jump test, stranding broad jump test and dollyo chagi test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is the correlation exsplosive power leg muscles with dollyo chagi kick of Taekwondo Athlete of pekanbaru, which shows α (0,05) = rhitung(0,769)> rtabel(0,602)..Key word : explosive power leg muscles, circular kick.